Activity Approach to Reflection of Ideas Formats of Thinking - Urozov Shahobiddin Ziyadullayevich (International Journal on Human-Computing Studies, 2022)
The article focuses on the enrichment of modern science and philosophy with new concepts, ideas and approaches, the content of such concepts as "format", "thinking format", "cognitive formatting, etc.", which are more common in the context of innovative conceptual trends.